An approach to a geropsychiatric assessment - Sandeep Grover; Ajit Avasthi (Journal of Geriatric Mental Health)
The psychiatric assessment of elderly differs from assessment of adult patients on various accounts. In this continuing medical education series, we discuss the generic aspects of psychiatric assessment of elderly. In this document we describe the SAFEST approach for psychiatric evaluation of elderly. This involves understanding the signs and symptoms [S], Additional Diagnosis- comorbid physical and psychiatric diagnosis [A], level of functioning, frailty, falls, forceful acts-abuse, forensic issues [F], collecting extra information pertaining to nutritional status, the environment in which the patient is living, constipation, urinary symptoms (incontinence/retention), and weight loss [E], understanding the ongoing stressors, suicidality, substance use disorder, sleep-related issues, sexual history, supervision of medication, safety issues, social support, spirituality and religiousness [S] and collecting the treatment history [T]. Clinicians should also give due importance to physical examination. While carrying out the mental status examination due importance must be given to assessment of cognitive functions. Basic investigations must be carried out in all the elderly patients, whenever feasible before starting psychotropic medications. A detailed case formulation should be made by taking the history, physical examination findings, mental status examination findings and the investigations.